Pers Sebagai Pilar Demokrasi dalam Perspektif Islam - Josua Satria Collins (Jurnal Hukum Lex Generalis, 2021)
Democracy makes the press the most effective communication medium. In Islam, Qur’an has regulated how the press should move and develop. In the midst of the digital era, the diversity of communication and information networks naturally challenges the Islamic Press to be active and wise. The author wants to find out why the press is an important part of democracy and how the concept of the press is from an Islamic perspective. Through secondary data analysis, it was found that the press within the framework of democracy acts as a civic forum, government watchdog, and agent for mobilizing citizen support. The Islamic press has become a tool for educators (Muaddib), information officers (Musaddid), reformers (Mujaddid), unifier (Muwahid), and fighters (Mujahid). If the actors of the Islamic Press are able to maintain their potential and character, then the Islamic mass media will remain strong.